2009
DOI: 10.1097/qai.0b013e318198a0cc
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Switching Nevirapine Twice Daily to Nevirapine Once Daily in Virologically Suppressed Patients

Abstract: In patients on standard twice daily NVP-containing regimens for at least 12-18 weeks, per protocol analysis showed that switching to once daily NVP was not inferior to continued twice daily NVP in terms of the predefined noninferiority margin of 10% for hepatotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Moreover, liver toxicity associated with the use of ARV drugs is usually somewhat higher in patients coinfected with HCV [4]. Most cases of NVP-associated hepatotoxicity appear during the first 2 to 3 months of therapy and manifest as a hypersensitivity reaction [14][15][16][17]. This clinical syndrome seems to be more frequent in patients with certain genetic markers [14], and is mainly driven by the presence of high CD4 counts (>400 cells/μL in men and >250 cells/μL in women), mostly in patients with detectable viral load [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, liver toxicity associated with the use of ARV drugs is usually somewhat higher in patients coinfected with HCV [4]. Most cases of NVP-associated hepatotoxicity appear during the first 2 to 3 months of therapy and manifest as a hypersensitivity reaction [14][15][16][17]. This clinical syndrome seems to be more frequent in patients with certain genetic markers [14], and is mainly driven by the presence of high CD4 counts (>400 cells/μL in men and >250 cells/μL in women), mostly in patients with detectable viral load [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hepatotoxicity with 400-mg once-daily dosing appears to be low when CD4 T-cell thresholds (see below) and 14-day dosage escalation guidelines are followed [5]. One study showed safety of switching from 200 mg twice daily to 400 mg once daily after at least 12 to 18 weeks of therapy [6]. With the ER formulation, 400 mg once daily should begin immediately after the aforementioned 14-day lead in.…”
Section: Overview Of Nevirapine and Its Pharmacologymentioning
confidence: 99%
“…Se demostró también, que la formulación de liberación sostenida mantuvo concentraciones constantes entre las dosis. Estaría indicada en adultos que están recibiendo nevirapina por más de 12 a 18 semanas 26,27 .…”
Section: Nevirapina (Nvp)unclassified